Boston and the making of a global city / James C. O'Connell. - O'Connell, James C. (University of Massachusetts Press, 2025)
In the late twentieth century the American and global economy shifted from manufacturing toward a knowledge industry. Following an economic low point several decades earlier, the city of Boston took advantage of the new era of globalization, fueled by dramatic advances in telecommunications, computer power, and air and sea travel, as well as its own impressive intellectual capital. 'Boston and the Making of a Global City' pulls together scholarship, media stories, personal interviews, and city planning documents to tell the story of Boston's historical trajectory, as it quickly became a competitive global hub.